Faktor Penarik Anak Sebagai Pelaku Tindak Kekerasan di Sekolah - Fitri Noviyanti; Sindy Arzety Yusuf; Sovi Ayudia Putri (Universitas Sains dan Teknologi Komputer, 2023)
The involvement of children in criminal cases in the school environment is generally quite odd in society. This raises various questions about what factors can make children the main perpetrators of criminal acts. There are several factors that can motivate a person to commit a criminal act, including; unstable mentality, psychological and socioemotional. In addition to the influence of the negative impact provided by the abuse of electronic media and demands on children, this has become a polemic that is difficult to overcome among Indonesian children, for example the case that occurred in Cilacap, Central Java. The number of crimes committed by children every turn of the year is still in an alarming number. Analysis of data delivery is carried out using descriptive methods by making descriptions or descriptions of the background of events found in loading primary and secondary data, which are then analyzed with a comprehensive narrative, namely the background of violence and crime in children in the Cilacap area, Central Java; factors of education, environment, weak handling of cases of violence in schools, and also cannot be separated from parental negligence.